2022
DOI: 10.3390/jcm11123262
|View full text |Cite
|
Sign up to set email alerts
|

Is Bilirubin Associated with the Severity of Ischemic Stroke? A Dose Response Meta-Analysis

Abstract: There is no consensus on the role of bilirubin in acute ischemic stroke. Higher levels of serum bilirubin may provide a treatment advantage in oxidative-stress-mediated diseases but also may simply reflect the strength of the oxidative stress. As of 28 February 2022, the relevant studies were selected from four databases (PubMed, Web of science, Cochrane, and CNKI) through a retrieval strategy, and strict literature screening and quality evaluation were carried out. The dose–response relationship was fitted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…In addition to diagnostic value, we investigated the prognostic value of bilirubin subtypes in ischemic stroke. Our results determined that the direct and total bilirubin levels were positively correlated with the ischemic stroke severity, consistent with the systematic review of Ghojazadeh et al's (2020) study and Song et al's (2022) study. Song et al also established that bilirubin is linear with ischemic stroke severity and trial sequential analysis found that the sample size for this study is sufficient.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to diagnostic value, we investigated the prognostic value of bilirubin subtypes in ischemic stroke. Our results determined that the direct and total bilirubin levels were positively correlated with the ischemic stroke severity, consistent with the systematic review of Ghojazadeh et al's (2020) study and Song et al's (2022) study. Song et al also established that bilirubin is linear with ischemic stroke severity and trial sequential analysis found that the sample size for this study is sufficient.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is strong evidence that bilirubin has anti-inflammatory, antioxidant, and neuroprotective properties ( Thakkar et al, 2019 ). Previous meta-analyses suggested that a higher total level of bilirubin was related to a lower stroke prevalence and had a significant association with stroke severity, indicating that bilirubin might be involved in the progression of stroke ( Zhong et al, 2019 ; Song et al, 2022 ). Recently, however, there has been no definitive consensus on the relationship of bilirubin levels with stroke risk ( Page et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the prognostic values of bilirubin in stroke are controversial, since bilirubin exhibits both neuroprotective and neurotoxic effects. At least two studies validated that TBIL and DBIL levels were significantly and positively associated with stroke severity [71,73]. Moreover, Ouyang et al [74] demonstrated that elevated levels of serum TBIL, DBIL and IBIL were significantly associated with poor functional outcomes in patients with AIS or TIA at 3-month and 1-year follow-ups.…”
Section: Discussionmentioning
confidence: 97%
“…Stroke is considered the second leading cause of death worldwide and remains a significant cause of disability in both developed and developing countries (1). Ischemic stroke accounts for almost 70% of all stroke cases (1).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is considered the second leading cause of death worldwide and remains a significant cause of disability in both developed and developing countries (1). Ischemic stroke accounts for almost 70% of all stroke cases (1). There is a rich literature available substantiating that prolonged sleep onset latency (PSOL) and age can determine stroke severity (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%